Textural Behavior of Ripening Sapota. Fruits - B Raharjo; Tranggono Tranggono; J. S. Dethan (Indonesian Association of Food Technologists, 1998)
Physical quality of fruits is commonly determined by their texture. The texture of fruits often depends on its maturity level. Generally the texture of fruits is quantified by their firmness that is defined as the force to attain certain deformation. However fruits can not be considered as simple elastic materials. They are more appropriately considered as non linear viscoelastic objects with three parameters. Accordingly the objectives of the study were to determine the viscoelastic parameters of fruits by impact and to relate those parameters to the sensory evaluations of the maturity of the samples. Samples were sapota fruits stored and ripened at mom temperature. The samples Were impacted onto hard surface and the impact forces were recorded using a computer. The impact forces were analyzed to determine the viscoelastic parameters. The maturity indices of the samples were determined by sensory evaluation and then compared to the impact parameters. The results indicated that the impact parameters can be related to the maturity index. It seems that the maturity of fruits can be determined by impact.